Health research production in developping countries/africa - Aisha Nasef; Adel El-Taguri (Annals of Bone Marrow Research - Peertechz Publications, 2020)
Qualified researchers from Africa, who worked in team abroad are competent. But, they cannot reproduce and develop works started abroad after returning back to home countries.  In this article we will list briefly the different underlying causes, challenges, consequences and future aspiration.